ANALYSIS OF HUMOR AND HUMOROUS IMAGERY IN DR.SEUSS’S “THE CAT IN THE HAT” (International journal of medical sciences, 2025)
This article examines humor, satire, literary devices, anthropomorphism, and political symbolism in The Cat in the Hat. Through the Cat and the fish, the narrative addresses morality, responsibility, childhood psychology, and social norms.